Stem Cell-Derived Models of Neural Crest Are Essential to Understand Melanoma Progression and Therapy Resistance - Larribère, Lionel; Utikal, Jochen (Frontiers in Molecular Neuroscience, 2019)
During development, neural crest (NC) cells are early precursors of several lineages including melanocytes. Along their differentiation from multipotent cells to mature melanocytes, NC cells will go through successive steps which require either proliferative or motile capacities. For example, they will undergo Epithelial to Mesenchymal Transition (EMT) in order the separate from the neural tube and migrate to their final location in the epidermis (Larribere & Utikal, 2013; Skrypek, Goossens, De Smedt, Vandamme, & Berx, 2017). The differentiated melanocytes are the cells of origin of melanoma tumors which progress through several stages such as radial growth phase, vertical growth phase, metastasis formation, and often resistance to current therapies. Interestingly, depending on the stage of the disease, melanoma tumor cells share phenotypes with NC cells (proliferative, motile, EMT). These phenotypes are tightly controlled by specific signaling pathways and transcription factors which tend to be reactivated during the onset of melanoma. In this review, we summarize first the main transcription factors which control these common phenotypes. Then, we focus on the existing strategies used to generate human neural crests. Finally we discuss how identification and regulation of neural crest-associated genes provide an additional approach to improving current melanoma targeted therapies.